Evaluation of Acute Toxicity of Aqueous Extract of Libyan Globularia Alypum in Albino Mice - Suad Shanab; Abdulruzag Auzi (Khalij-Libya Journal of Dental and Medical Research, 2022)
Aims. Lorke’s method was used to evaluate the acute toxicity effect of aqueous extract from the aerial part of Libyan Globularia alypum on albino mice. Methods. The study involved intra-peritoneal administration of different doses of the extract to groups of female mice. Results. Signs resultant toxicity and possible death of animals were monitored for 14 days to ascertain the median lethal dose (LD50) of the extract. At the end of the two-week study, all the animals in all the dose groups were survived. Conclusion. Globularia alypum plant can be considered as safe plant, as long as the LD50 is greater than 5000 mg/kg body weight.